Purple Urine Bag Syndrome. Report of One Case [Síndrome de la Bolsa de Orina Púrpura: Un Fenómeno Inusual y Muy Llamativo] - Chassin-Trubert-Contreras, A (Sociedad Medica de Santiago, 2014)
Purple urine bag syndrome is an uncommon but particularly striking phenomenon observed in people with urinary catheters and co-existent urinary tract infections. A chemical reaction between plastic and certain bacterial enzymes results in an intense purple urine color. We report a 72 year-old male with a cystostomy. A purple coloration of his urinary drainage bag and tubing was noted in the context of a urinary tract infection caused by Citrobacter freundii. © 2014 Sociedad Medica de Santiago. All rights reserved.